Antibody response and clinical reactions in children given measles vaccine with immunoglobulin. Issue 6527 (19th April 1986) - Lingam, S; Miller, C L; Clarke, M; Pateman, J
Abstract : Antibody responses and clinical reactions to three measles vaccines (Attenuvax, Mevilin, and Rimevax) injected into the opposite arm to immunoglobulin were assessed in 45 children with brain disorders making them susceptible to fits if given measles vaccine alone. In this small study no unacceptable reactions occurred and in only three cases was the antibody response minimal or absent. More children in this special category should be considered for vaccination against measles in this way.